An analysis of contagion effect on ASEAN stock market using multivariate markov switching DCC GARCH - Terdthiti Chitkasame (2019)
© 2019 by the Mathematical Association of Thailand. All rights reserved. Contagion effect is a transmission of volatility from shocks arising in one country to other countries. Volatility transmission particularly occurs in emerging countries like the ASEAN. In this study, we investigate the contagion effect in eight stock of the South East Asia stock markets (ASEAN), namely stock exchange of Thailand (SET), Indonesia stock exchange (IDX), Hanoi stock exchange (HNX), Kuala Lumpur Stock Exchange (KSX), Singapore Exchange Limited (STI), The Philippine Stock Exchange, Inc. (PSEi), Cambodia Securities Exchange (CSX) and Lao PDR stock exchange (LSX) (which call ASEAN stock markets). The contagion effect is investigated using correlation analysis, thus, we employ the MS-DCC-GARCH model. The result of this research shows that ASEAN stock markets usually stay in high correlation regime and the degree of volatility is high. This indicates a strong contagion among ASEAN stock markets.